Kepercayaan Air Suci Kalibacin: Sebuah Kajian Antropologi Budaya dan Agama Masyarakat Banyumas - Meti Muji Pangestika; M. Slamet Yahya (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
This research aims to understand Kalibacin holy water beliefs in the cultural and religious context of the Banyumas community. This research was conducted using qualitative methods, which included participant observation, in-depth interviews, and document analysis. The research results show that the Kalibacin holy water belief has long historical roots and is closely related to the culture and religion of the Banyumas people. This belief is believed to have the power to cure disease, provide good luck, and protect from danger. Kalibacin holy water is obtained by performing a special ritual at the Kalibacin spring, which is located in Kalibacin Village, Banyumas District, Banyumas Regency. This ritual is led by a caretaker, who is a descendant of the founder of the Kalibacin spring. The Kalibacin holy water belief has a deep symbolic meaning for the people of Banyumas. Kalibacin holy water is considered an embodiment of purity and supernatural power. This belief also functions as a tool to strengthen social solidarity and cultural identity of the Banyumas people. This research has important implications for understanding the culture and religion of the Banyumas people. This research shows that the Kalibacin holy water belief is an integral part of the lives of the Banyumas people and has an important role in preserving local culture and religion.